RESPON PERTUMBUHAN DAN PRODUKSI BERBAGAI RUMPUT LOKAL YANG DIPUPUK DENGAN PUPUK NPK - i Gd. O.J., Asmara; Puger, A. W.; Kusumawati, N. Nym. C. (Jurnal Peternakan Tropika, 2019)
The study aims to obtain information about the effect of various dosage on the growth and production of various local grasses that are fertilized with NPK fertilizer. The study is carried for 10 weeks. The design  used is a complete randomized design (RAL) with spit plot pattern of local grass type as main plot, that are Stenotaphrumsecundatum, Axonopusscompressus and Paspalum conjugatum with NPK fertilizer dosage. as subplots, that are 0 g/pot, 0.1 g/pot, 0.2 g/pot and 0.3 g/pot, The experiment was repeated four times so there are 48 experiment units. Thevariables observed were plant length, number of leaf, number of tiller, leaf dry weight, dryweight of stem, root dry weight, total dry weight of forage, leaf dry weight ratio with dry weightof stem, total dry weight of forage ratio with root dry weight top root ratio) and leaf area per pot.The results showed that dosage of fertilizer was not significantly different (P>0.05) to plant lengthvariables, number of leaf, number of tiller, leaf dry weight, dryweight of stem, total dry weight of green, leaf dry weight ratio with dry weightof stem, total dry weight ratio of forage with root dry weight top root ratio) and leaf area, but significantly different (P<0.05) on root dry weight. In different types of plants (P <0.05) to plant length variables, number of leaf, leaf dry weight, dryweight of stem, total dry weight of forage, total dry weight ratio of forage with root dry weight top root ratio, leaf area and not significantly different (P>0.05) number of tiller,root dry weight, leaf dry weight ratio with dry weight of the stem. Based on the result of research, it can be concluded that dosas of fertilizer D3 =0,3g/pot and Stenotaphrumsecundatum grass response to the best growthand production response and thereis no interaction between dosage of fertilizer wite grass type.  Keywords: local grass, doses of fertilizer, growth, production